2012
DOI: 10.2478/v10202-011-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Immigrants, Visible Expats?: <i>Americans in Finnish discourses on immigration and internationalization</i>

Abstract: This article examines contemporary immigration discourses in Finland using experiences of immigrants originating from the United States as a case study. This research shows that the notion of an "immigrant" (maahanmuuttaja) is a highly racialized and class-based category in Finland. The difficulties of finding work that fits Americans' educational qualifications and their discouraging experiences of speaking "broken Finnish" reveal the fluidity of the division between foreigners who are seen as immigrants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 16 publications
2
57
0
1
Order By: Relevance
“…Therefore, Koreans as "visible" or "marked" immigrants compared with Anglo-Americans. The immigrants' visibility is subject to each country and to the relationship between the host country and the migrants' country, as Leinonen (2012) showed in her study of white American expatriates in Finland. For example, White Americans are located in various domains of immigrant visibility in Finland-for example, with one domain including those who are visually identified as immigrants-and at the level of public and academic discussions on immigration.…”
Section: Being "White" or "Indian": Racial Reassignment Of Latin Amermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Koreans as "visible" or "marked" immigrants compared with Anglo-Americans. The immigrants' visibility is subject to each country and to the relationship between the host country and the migrants' country, as Leinonen (2012) showed in her study of white American expatriates in Finland. For example, White Americans are located in various domains of immigrant visibility in Finland-for example, with one domain including those who are visually identified as immigrants-and at the level of public and academic discussions on immigration.…”
Section: Being "White" or "Indian": Racial Reassignment Of Latin Amermentioning
confidence: 99%
“…For example, De Genova and Ramos-Zaya (2003) demonstrated that Latinos from various countries attempted hierarchical reassignment in a factory in Chicago in consideration of their U.S. racial classifications according to the meaning of U. S. citizenship. Leinonen (2012) demonstrated that White Americans are located in various domains of immigrant visibility in Finland. Likewise, when several ethnic and racial groups of Latin Americans come to Korea, they might locate themselves differently, according to how Korea sees them.…”
mentioning
confidence: 99%
“…I draw on previous research on integration and how it relates to language learning (Anthias, Kontos & Morokvasic-Müller, 2013;Kärkkäinen, 2011;Pöyhönen & Tarnanen, 2015;Simpson & Whiteside, 2015;Veikou 2013), the changing understanding of language (Canagarajah, 2013;Garcia & Wei, 2014;Pennycook, 2010), studies of ELF (Jenkins, 2007;Seidlhofer, 2011) and the connection between language practices and experiences of inclusion (Delanty, Jones & Wodak, 2008;Latomaa, 1998;Leinonen, 2012;Leppänen, Nikula & Kääntä, 2008). The data consists of interviews with eight stay-at-home parents of migrant background.…”
Section: Apples -Journal Of Applied Language Studiesmentioning
confidence: 99%
“…(Delanty et al, 2008, p. 3) Although English has no official status in Finland, it is the most widely studied and commonly used foreign language and it is considered an essential resource in the increasingly multicultural and globalizing world (Leppänen et al, 2008). According to Leinonen (2012), this is indeed (at least part of) the problem: discourses related to immigrant integration on the one hand and the internationalization of the Finnish society on the other hand are separate, and seem to lead in quite different directions. Leinonen's study focused on Americans living in Finland and she found that in some contexts, Americans were perceived as 'elite' migrants because of being native speakers of English, but for example when entering the job market, their lack of local language skills was a potential drawback signaling immigrant status.…”
Section: Language Practices As a Basis For Migrant Inclusion And Exclmentioning
confidence: 99%
“…The term "immigrant" therefore implies deviating visually from the majority norm: being "visible". Although the notion of migrant (in) visibility is frequently used to refer to migrants' marked or unmarked embodiment (Mas Giralt 2011: 331), the term has also been used with a wider reference and can, for example, also refer to visibility in public discourses and to being visible (audible) through language use (Leinonen 2012). (In)visibility varies depending on context.…”
Section: (In)visibility and Whitenessmentioning
confidence: 99%